Rearing background and exposure environment together explain higher survival of aquaculture fish during a bacterial outbreak - Räihä, Ville; Sundberg, Lotta‐Riina; Ashrafi, Roghaieh; Hyvärinen, Pekka; Karvonen, Anssi
2019